REORIENTASI KEDUDUKAN QANUN NO. 6 TAHUN 2014 TENTANG HUKUM JINAYAH DALAM KAITANNYA DENGAN KONSEP HAK ASASI MANUSIA MENURUT HUKUM ISLAM DAN BARAT - Ferizal, Indis (IAIN Langsa, 2016)
The existence of Qanun Jinayat No. 6 Year 2014 in Aceh as a form of special autonomy related to the concept of international human rights should adapt to International Human Rights implementation, because Aceh?s Qanun Jinayat belongs to the legal order of Indonesia even though it applies spesifically and it  must adjust with National law enforcement, and Indonesia is one of  the state in the world that agrees to The International Human Rights law implementation.